Vox regis : royal communication in high medieval Norway - Brégaint, David (Northern world ;, 2016)
In Vox regis: Royal Communication in High Medieval Norway , David Brégaint examines how the Norwegian monarchy gradually managed to infiltrate Norwegian society through the development of a communicative system during the High Middle Ages, from c. 1150 to c. 1300. Drawing on sagas, didactic literature, charters, and laws, the book demonstrates how the Norwegian kings increasingly played a key -role in the promotion of royal ideology in society through rituals and the written word. In particular, the book stresses the interaction between secular and clerical culture, the role of the Church and of the Norwegian aristocracy.